CO2 storage capacity estimation in oil reservoirs by solubility and mineral trapping. (February 2018) - Ding, Shuaiwei; Xi, Yi; Jiang, Hanqiao; Liu, Guangwei
Abstract: Oil reservoirs are considered good storage sites for CO2 storage and sequestration. Previous analysis has evaluated CO2 storage capacity by using a wide variety of approaches and methodologies that considered the structural and residual trapping mechanisms. However, there is few published analysis regarding the solubility and mineral trapping. The objective of this paper is to estimate the storage capacity of CO2 sequestered in oil reservoirs by solubility and mineral trapping. The methodology of storage capacity of CO2 solubility in remaining oil, formation water and by mineral trapping is first presented. Then the implementation of methodology for estimating the storage capacity of HB oil field in China is discussed. Field-scale case study shows that the theory storage capacity by solubility in remaining oil of HB oil field is approximately 2.82 Mt and by solubility in formation water is approximately 0.48 Mt. The solubility coefficient of remaining oil (0–10) is much higher than that of formation water (0–0.1), which indicates the solubility principle "like dissolves like". The variation laws are all consistent with the rules published before. Injecting the CO2 into the reservoir with high pressure and low temperature might sequestrate more CO2 . The most effective factors of CO2 solubility in formation water is the temperature, salinity, and finally the pressure. Moreover, the mineral trapping evaluation results of HB oil field shows that the theoretical maximum storage capacity calculated by Xu et al. (2004) and our proposed method are approximately 18.9 Mt and 18.2 Mt CO2, respectively, with a relative error of about 3.7%. However, our proposed method could obtain the annual quantity of CO2 that could be sequestered by mineral trapping which is more superior. Overall, the proposed method is quite accurate and practical with high credibility. Highlights: A CO2 geological storage methodology based on solubility trapping is proposed. The methodology of storage capacity of CO2 by mineral trapping is presented. The solubility coefficient of remaining oil is higher than that of formation water. The annual quantity of CO2 sequestered by mineral trapping can be obtained.